Competency assessment in fraud detection at BPK: Challenges and enhancements - Sukma, Dadang; Wardhani, Ratna (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
Public concerns have been raised regarding the audits conducted by the Audit Board of the Republic of Indonesia (Badan Pemeriksa Keuangan or BPK), the supreme audit institution, which often issues unqualified opinions despite the increasing number of corruption cases. Internally, BPK recognizes this issue as a critical risk that must be mitigated to preserve public trust. BPK must maintain its competence and safeguard public funds. This case evaluates auditors’ competency levels, identifies internal factors supporting their competence, and examines BPK’s initiatives for improving fraud detection skills. Using survey, interview, and document review data, this case study assesses competency according to BPK standards. It investigates internal factors through the auditor's code of ethics and reviews performance reports to evaluate fraud detection skills. Our study finds that BPK auditors possess strong fraud detection skills. Second, the key internal factors strengthening fraud detection include competence and professional due care. Third, BPK has introduced limited education, training, and CFE/CFrA certification policies. Senior fraud detection auditors report feeling more competent due to their increased training, experience, and access to certifications. This study employs novel internal standards, self-assessment surveys, and interviews to analyze fraud detection proficiency.